Burrokeet - Gardler, Ross; Singh, Rajendra G.; Cummings, Thompson; Ramanan, Anil; Mohammed, Shareeda; Bernard, Margaret; Rudder, Andrew (My University, 2010)
This item relates to the development and deployment of an open-source Learning Content Management System called Burrokeet.
Keywords: Shareable learning objects; Computer science course; Caribbean education; Instructional design; Blended learning; Hybrid instruction; Web-based instruction; Learning content management systems; Web-based education; Visualization; Computer programming